The politics of international marriage in Japan - Kim, Viktoriya; Balgoa, Nelia G.; Yamamoto, Beverley (Politics of marriage and gender, 2022)
"This book provides an in-depth exploration and analysis of marriages between Japanese nationals and migrants from three broad ethnic/cultural groups - spouses from the former Soviet Union countries, the Philippines, and Western countries. It reveals how the marriage migrants navigate the intricacies and trajectories of their marriages with Japanese people while living in Japan. Seen from the lens of 'gendered geographies of power', the book explores how state-level politics and policies towards marriage, migration, and gender affect the personal power politics in operation within the relationships of these international couples. Overall, the book discusses how ethnic identity intersects with gender in the negotiation of spaces and power relations between and amongst couples; and the role states and structural inequalities play in these processes, resulting in a reconfiguration of our notions of what international marriages are and how powerful gender and the state are in understanding the power relations in these unions"--